2013
DOI: 10.18632/oncotarget.901
|View full text |Cite|
|
Sign up to set email alerts
|

Actin-binding protein alpha-actinin 4 (ACTN4) is a transcriptional co-activator of RelA/p65 sub-unit of NF-kB

Abstract: ACTN4 is an actin-binding protein that participates in cytoskeleton organisation. It resides both in the cytoplasm and nucleus and physically associates with various transcription factors. Here, we describe an effect of ACTN4 expression on transcriptional activity of the RelA/p65 subunit of NF-kB. We demonstrate that ACTN4 enhances RelA/p65-dependant expression of c-fos, MMP-3 and MMP-1 genes, but it does not affect TNC, ICAM1 and FN1 expression. Importantly, actin-binding domains of ACTN4 are not critical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 59 publications
(73 reference statements)
3
50
0
1
Order By: Relevance
“…It is known that actively transcribed genes are enriched in actin-containing nuclear matrix, and that chromatin remodeling SWI/SNF complex is associated with nuclear actin (51). Moreover, recent work has shown that ACTN4 is associated with the activated nuclear NFB transcriptional factor as a gene-specific coactivator (52). More work will be required to understand the relationship between the cytoskeleton, CDK9, and mRNA processing in inducible gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that actively transcribed genes are enriched in actin-containing nuclear matrix, and that chromatin remodeling SWI/SNF complex is associated with nuclear actin (51). Moreover, recent work has shown that ACTN4 is associated with the activated nuclear NFB transcriptional factor as a gene-specific coactivator (52). More work will be required to understand the relationship between the cytoskeleton, CDK9, and mRNA processing in inducible gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found a continuous (6 and 12 weeks) upregulation in the expression of alpha-actinin ACTN4 and increased expression of ACTN1 only at the later stage (12 weeks). As the previously mentioned SYNPO protein, these alphaactinins are actin-binding proteins that belong to the spectrin superfamily and play a crucial role in remodeling of actin-cytoskeleton [63]. Alterations in actin dynamics have been observed in senescence and may affect endothelial sensing of shear stress [64].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to hormone-dependent interaction between ACTN4 and nuclear receptors, this finding provides an alternative mechanism by which ACTN4 potentiates transcriptional activity. A previous study has suggested a role of ACTN4 in activating NF-B activity (28). However, it was concluded that ACTN4 and NF-B interact in the cytoplasm, and it is unclear how cytoplasmic ACTN4 potentiates NF-B activity.…”
Section: Actn4 Is a Transcriptional Coactivator Of Nf-bmentioning
confidence: 98%